The vision of on-demand architectural knowledge systems as a decision-making companion - Razavian, Maryam; Paech, Barbara; Tang, Antony (The journal of systems and software, 2023)
Cobbler’s children do not wear shoes. Software engineers build sophisticated software but we often cannot find the needed information and knowledge for ourselves. Issues are the amount of development information that can be captured, organizing that information to make them useable for other developers as well as human decision-making issues. Current architectural knowledge management systems cannot handle these issues properly. In this paper, we outline a research agenda for intelligent tools to support the knowledge management and decision making of architects. The research agenda consists of a vision and research challenges on the way to realize this vision. We call our vision ondemand architectural knowledge systems (ODAKS). Based on literature review, analysis, and synthesis of past research works, we derive our vision of ODAKS as decision-making companions to architects. ODAKS organize and provide relevant information and knowledge to the architect through an assistive conversation. ODAKS use probing to understand the architects’ goals and their questions, they suggest relevant knowledge and present reflective hints to mitigate human decision-making issues, such as cognitive bias, cognitive limitations, as well as design process aspects, such as problem-solution coevolution and the balance between intuitive and rational decision-making. We present the main features of ODAKS, investigate current potential technologies for the implementation of ODAKS and discuss the main research challenges.
Available online 25 November 2022
Gesehen am 27.02.2023